Perceptions of Employability Skills for Youth Employment: A Comparative Study between Youth and Employers in Malaysia - ABU SEMAN, NOOR ASLINDA (Research in Management of Technology and Business, 2023)
This paper addresses the pressing issue of youth unemployment in Malaysia and the mismatch between their skills and employers’ demands. The study aims to explore how both youth and employers perceive the importance of employability skills crucial for youth to secure employment. The research is driven by the growing recognition that youth employability skills are pivotal for successful workforce integration. The study employed quantitative methods and collected data through cross-sectional surveys from youth (aged 18-30) and employers in Batu Pahat, Johor. The findings revealed that youth participants emphasize a diverse range of employability skills, with Personal Quality Skills ranking highest, followed by Resource and Capability Skills, Information Skills, Basic Skills, Interpersonal Skills, Thinking Skills, and System and Technology Skills. Employers, on the other hand, rated Basic Skills as the most essential, followed by Personal Quality Skills, Resource and Capability Skills, Thinking Skills, Interpersonal Skills, Information Skills, and System and Technology Skills. The findings underscore the importance of a strong skill set for youth employability, emphasizing the need for aligning education with industry demands and fostering relevant skills to enhance job prospects. Ultimately, this research sheds light on the critical role of employability skills in addressing youth unemployment challenges and bridging the gap between industry expectations and young job seekers’ skills.